Innovations in monoclonal antibody-based multipurpose prevention technology (MPT) for the prevention of sexually transmitted infections and unintended pregnancy - Sarah Dohadwala; Matthew T. Geib; Joseph A. Politch; Deborah J. Anderson; Deborah J. Anderson (Frontiers in Reproductive Health, 2024)
Monoclonal antibodies (mAbs) are currently being produced for a number of clinical applications including contraception and the prevention of sexually transmitted infections (STIs). Combinations of contraceptive and anti-STI mAbs, including antibodies against HIV-1 and HSV-2, provide a powerful and flexible approach for highly potent and specific multipurpose prevention technology (MPT) products with desirable efficacy, safety and pharmacokinetic profiles. MAbs can be administered systemically by injection, or mucosally via topical products (e.g., films, gels, rings) which can be tailored for vaginal, penile or rectal administration to address the needs of different populations. The MPT field has faced challenges with safety, efficacy, production and cost. Here, we review the state-of-the-art of mAb MPTs that tackle these challenges with innovative strategies in mAb engineering, manufacturing, and delivery that could usher in a new generation of safe, efficacious, cost-effective, and scalable mAb MPTs.